The Law of Oil and Gas in Uganda - Lubogo, Isaac Christopher (Jescho Publishing House, 2021)
The nature of oil and gas is one that is wide. As an industry, it covers very many areas of the economy and the social structure. It is concerned with the community; the people who are affected by the work it does. This is because the industry must acquire land or work side by side with the communities in order to extract oil. In this process, the industry must be careful to establish a working relationship between themselves and the communities concerned. The oil and gas industry also concerns the environment and its sustainability. This paper found that the work carried out by the oil and gas sector has a direct impact on the well-being of the environment. Poor working mechanisms could potentially harm the environment. The industry can pollute air, land and water bodies thereby choking the surrounding environments of their existence and well-being. The industry is also concerned with the welfare of its own workers. It must be able to respect and uphold their health and safety while at work or risk facing court cases that will usually require compensation. The Oil and Gas sector is comprised of numerous contracts that must exist to set the project into action. These contracts are principally between the IOC and the state that owns the resource. They can also be contracts between the IOCs and different subsidiary companies whose role is to carry out certain activities that the IOC could not carry out on its own. The oil and gas mining is a venture that takes up a long amount of time. The bringing of oil to fruition can take years of hard work and as such, there is an investment that must be made at the early stages. This investment can only be regained at the end of the exhaustion of the project. This is why the sector is very sensitive to changes in laws and taxation regimes as we know them. If these changes occur to the sector without rightful insurance, it becomes difficult to see the possibility of reaping from the sector. The exploitation of Oil and Gas has extensive bearings upon the Communities where the oil is situated. The settlers in the Albertine region have so far been affected by the exploration stages of production. Some have been asked to relocate, with or without compensation. Some have been resettled to other parts in the country for purposes of exploration. This is because of the effects the processes of the mining could potentially have on their health and the environment at large. The environment and climate are usually not spared in this too and as such, many measures must be put in place to preserve the environment as much as is possible during these processes of exploitation of the resource. These measures include the passing or updating of laws concerned with environmental management, and ratifying of international instruments that protect the same. Also, the production of Oil undergoes different stages of production. The Upstream which entails the exploration and drilling of the oil; midstream which is concerned with transportation of this oil to refineries for purifying; and then downstream which is concerned with the marketing and sale of the product. All these processes will in essence require a lot of contracts with many different organisations and many subcontracts as well. Some are straight up necessary; others are required by the law. All these factors; numerous contracts, upfront investment, long life span, sensitivity to change in laws and tax regimes, climate and community impact and different stages of production; increase the chances of disputes arising. Indeed, any of the mentioned factors has led to disputes that have required settlement. Oil exploration started way back in the early 347 AD in China. In East Africa, oil exploration started in the early 1930s by the British colonialists. The discovery of oil in South Sudan, in 1987 brought many prospects of oil discoveries in East Africa. 2006 massive oil reserves were discovered on the Ugandan shores of Lake Albert. However, the discovery of oil in Uganda is traceable far back before independence. Oil exploration activities were started in the 1920s by W.J. Wayland, a Colonial Government Geologist of the British Protectorate. The first well was drilled at a place called Butiaba-Waki in 1938. However, the activities did not solemnize due to the outbreak of the Second World War in the 1940s and the political instabilities of in the 1960s -1970s. These activities were resumed in 1983, leading to confirmation of the presence of oil in reasonable commercial reserves. The first recoverable oil discovery was made in 2006 by Hardman Petroleum and Energy Africa (now Tullow Oil) in Mputa-1 well Kaiso-Tonya. This brings the total discoveries of oil in Uganda to 21 to date. Oil and Gas Exploration in Uganda is currently taking place in the Albertine Graben region. This is part of the East African Rift System and runs along Uganda’s western border with the Democratic Republic of Congo (DRC). It is 500 km long and estimated to be 45 km in width. Amount of oil estimated to have been discovered is 6.5billion barrels. (I barrel is equivalent to 159 liters). Out of which 1.4 billion barrels is estimated as recoverable. The area explored presently represents less than 40% of the total area with the potential for petroleum production in the Albertine Graben and only 12% is licensed. There is therefore potential for additional petroleum resources to be discovered in the country when additional exploration is undertaken. It is important to note that not all that oil will be discovered. Globally, an average of 20%-30% of oil in place recovered economically using the available technologies.
Keywords: Petroleum law - Uganda; Oil and gas - Legal aspects; Oil and gas law - Uganda